Pusa Losar (BHS 380) – the first dual-purpose barley variety for northern hills of India - PAL, DHARAM; KUMAR, SANJAY; VERMA, R P S (The Indian Journal of Agricultural Sciences, 2012)
A new barley variety Pusa Losar (BHS 380), developed at Regional Station, Shimla, is released and notified by the Central Sub-Committee on Crop Standards, Notification and Release of Varieties for Agricultural Crops for commercial cultivation under rainfed condition of northern hills zone. The variety has average forage yield of 5.94 tonnes/ha along with average grain yield of 2.1tonnes/ha from the regenerated crop after cutting for forage. It has shown forage yield superiority over the checks and also grain yield superiority over HBL 276 in regenerated crop. This variety combines resistance against leaf and stripe rusts. Cultivation of newly released variety Pusa Losar (BHS 380) in north- western Himalaya would prove boon for meeting the forage and food requirements of the hilly people for sustaining their livelihood and stabilizing productivity of barley in the Himalayan region.